Children as Strategic Actors in Preschool Institutions - Manić, Ivana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper presents an analysis of the concept of a child as a strategic actor in preschool institutions and the opportunities for children to actively participate. The paper aimed to consider the understanding of children as competent social actors who actively participate in social life with different strategies and who change their social environment. After considering the concept of a child’s daily life and different environments in which children act, the analysis of the results of the research on children’s actions in preschool institutions is presented. Based on the available results, it can be concluded that there are opportunities for active strategic sharing of children in preschool institutions and that it is necessary to continue with their further development and improvement.
Keywords: everyday life; children’s actions; children as strategic actors; preschool institution